2017
DOI: 10.1002/pro.3213
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast‐localized small heat shock protein Hsp21 associates with the thylakoid membranes in heat‐stressed plants

Abstract: The small heat shock protein (sHsp) chaperones are crucial for cell survival and can prevent aggregation of client proteins that partially unfold under destabilizing conditions. Most investigations on the chaperone activity of sHsps are based on a limited set of thermosensitive model substrate client proteins since the endogenous targets are often not known. There is a high diversity among sHsps with a single conserved β‐sandwich fold domain defining the family, the α‐crystallin domain, whereas the N‐terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Oxidized methionines in VIPP1/2 and HSP22E/F might get re‐reduced by the action of a peptide methionine sulfoxide reductase (PMSR). This scenario has been proposed previously for Arabidopsis Hsp21 under heat stress conditions, during which two‐thirds of the otherwise stromal proteins re‐localize to thylakoid membranes (Bernfur, Rutsdottir, & Emanuelsson, ). Hsp21 has an N‐terminal amphipathic α‐helix harbouring six methionines that can get oxidized by H 2 O 2 and re‐reduced by a plastid PMSR (Gustavsson et al, ; Harndahl et al, ), suggesting an Hsp21 methionine sulfoxidation‐reduction cycle to quench reactive oxygen species (Sundby, Harndahl, Gustavsson, Ahrman, & Murphy, ).…”
Section: Discussionsupporting
confidence: 61%
“…Oxidized methionines in VIPP1/2 and HSP22E/F might get re‐reduced by the action of a peptide methionine sulfoxide reductase (PMSR). This scenario has been proposed previously for Arabidopsis Hsp21 under heat stress conditions, during which two‐thirds of the otherwise stromal proteins re‐localize to thylakoid membranes (Bernfur, Rutsdottir, & Emanuelsson, ). Hsp21 has an N‐terminal amphipathic α‐helix harbouring six methionines that can get oxidized by H 2 O 2 and re‐reduced by a plastid PMSR (Gustavsson et al, ; Harndahl et al, ), suggesting an Hsp21 methionine sulfoxidation‐reduction cycle to quench reactive oxygen species (Sundby, Harndahl, Gustavsson, Ahrman, & Murphy, ).…”
Section: Discussionsupporting
confidence: 61%
“…Importantly, studies using the transgenic tomato plants overexpressing HSP21 have shown that this protein associates with proteins of Photosystem II and does not reactivate heat-denatured Photosystem II, but instead protects this complex from damage during heat stress [ 150 ]. Interestingly, around two thirds of chloroplast HSP21 proteins are translocated into the thylakoid membranes in response to heat treatment in plants, suggesting that the association with membranes should be considered to fully understand the role of sHsps in physiological adaptation processes under stress conditions [ 151 ]. Despite extensive studies on HSP21, the specific roles of HSP21 in protecting PSII from heat stress remain elusive.…”
Section: Turnover Of Psii Core Subunits and Psii Protection Under mentioning
confidence: 99%
“…Hence, upregulation of AT5MAT may be an adaptive strategy of plants to cope with the toxic effects of insecticide [26]. Heat Shock Proteins (HSPs) are involved in the regulation of specific substrate proteins in stressful conditions especially under high temperature [27]. Under TXM application, some HSPs are also inhibited ( Fig.…”
Section: Discussionmentioning
confidence: 99%